Parent and Adolescent Interest in Receiving Adolescent Health Communication Information From Primary Care Clinicians - Ford, Carol A.; Cheek, Courtney; Culhane, Jennifer; Fishman, Jessica; Mathew, Leny; Salek, Elyse C.; Webb, David; Jaccard, James (Journal of adolescent health, 2016)
Patient-centered health care recognizes that adolescents and parents are stakeholders in adolescent health. We investigate adolescent and parent interest in receiving information about health topics and parent-teen communication from clinicians. Ninety-one parent-adolescent dyads in one practice completed individual interviews. Items assessed levels of interest in receiving health and health communication information from the adolescent's doctor about 18 topics, including routine, mental health, sexual health, substance use, and injury prevention issues. Analyses tested differences between parents and adolescents, within-dyad correlations, and associations with adolescent gender and age. Most parents were female (84%). Adolescents were evenly divided by gender; 36 were aged 12–13 years, 35 were aged 14–15 years, and 20 were aged 16–17 years. Adolescent race reflected the practice population (60% black; 35% white). The vast majority of parents and adolescents reported moderate or high levels of interest in receiving information about all 18 health issues and information to increase parent-teen communication about these topics. Parents' interest in receiving information varied by adolescent age when the expected salience of topics varied by age (e.g., acne, driving safety), whereas adolescents reported similar interest regardless of age. Adolescent gender influenced parent and adolescent interest. Level of interest in receiving information from doctors within adolescent-parent pairs was not significantly correlated for one-half of topics. Parents and adolescents want health care professionals to help them learn and talk about a wide range of adolescent health topics. Feasible primary care interventions that effectively improve parent-teen health communication, and specific adolescent health outcomes are needed.